Heterogeneity in the isolation of patches may be essential for the action of metacommunity mechanisms - Borthagaray, Ana I.; Cunillera-Montcusí, David; Bou, Jordi; Tornero, Irene; Boix, Dani; Anton-Pardo, Maria; Ortiz, Esteban; Mehner, Thomas; Quintana, Xavier D.; Gascón, Stéphanie; Arim, Matías (Frontiers in Ecology and Evolution, 2023)
The spatial isolation gradient of communities and the gradient in the species dispersal ability are recognized determinants of biodiversity in metacommunities. In spite of this, mean field models, spatially explicit models, and experiments were mainly focused on idealized spatial arrangements of communities leaving aside the combining role of dispersal and isolation gradients in metacommunity processes. Consequently, we have an incipient understanding of the role of real spatial arrangement of communities on biodiversity patterns. We focus on six metacommunities for which confident information about the spatial arrangement of water bodies is available. Using coalescent metacommunity models and null models that randomize the location of water bodies, we estimated the potential effect of the landscape on biodiversity and its dependence on species dispersal ability. At extremely low or high dispersal abilities, the location of ponds does not influence diversity because different communities are equally affected by the low or high incoming dispersal. At intermediate dispersal abilities, peripheral communities present much lower richness and higher beta diversity than central communities. Moreover, metacommunities from real landscapes host more biodiversity than randomised landscapes, a result that is determined by the heterogeneity in the geographic isolation of communities. In a dispersal gradient, mass effects systematically increase local richness and decrease beta diversity. However, the spatial arrangement of patches only has a large importance in metacommunity processes at intermediate dispersal abilities, which ensures the access to central locations but limits dispersal in isolated communities. The ongoing reduction in spatial extent and simplification of landscape may consequently undermine the metacommunity processes that support biodiversity, something that should be explicitly considered on preserving and restoring strategies.